The Effect of The Use of Tjong A Fie's Biography as A Social Studies Learning Resource on Multicultural Understanding and Student Tolerance - Fikriyandi, Luthfi; Saripuddin, Didin; Winarti, Murdiyah (Eduvest - Journal of Universal Studies, 2025)
Understanding tolerance and multiculturalism within Indonesia's diverse society is crucial in social science education. Social science learning should reflect real societal conditions, making it important to connect material content to students' environments. Utilizing the biography of Tjong A Fie, a significant figure in Medan, serves as an effective resource in this context. This study employed a quantitative approach with a quasi-experimental method at Al-Ulum Integrated Islamic Junior High School. Using random sampling, class VIII C was chosen as the experimental group, while class VIII E served as the control group. The treatment, conducted over three sessions, yielded positive results. The experimental class, using Tjong A Fie's biography, demonstrated significant improvement in multicultural understanding and tolerance, with a p-value of 0.000 < 0.005. The t-test results indicated t counts > t table, confirming the hypothesis that Tjong A Fie's biography positively impacts students' understanding of tolerance and multiculturalism. Additionally, the data showed normality and homogeneity, reinforcing these findings. The comparative analysis of pretest and posttest results revealed a significant difference between the control and experimental classes, with the control class averaging 71.00 and the experimental class averaging 85.5. This study underscores the effectiveness of incorporating Tjong A Fie's biography into social science curricula to enhance students' multicultural and tolerance understanding.